Adapting forests to climate change: an experiment to promote different tree species in mixed Scots pine forests (Pinus sylvestris L.) - Sara Buscà; Diana Pascual; Eduard Pla; Javier Retana (Annals of Forest Science)
Abstract Key message We have applied various silvicultural treatments to enhance the adaptation of Scots pine (Pinus sylvestris L.) mixed forests to climate change in Montesquiu Castle Park (Catalonia, NE Spain). Some treatments have shown positive effects, such as increased growth, reduced defoliation, and greater resistance of Scots pine to drought. However, other treatments may lead to a shift in vegetation from pine-dominated to oak-dominated forests. Future extreme droughts could increase pine mortality, potentially accelerating this shift. These findings are significant for forest management aimed at adapting these species to climate change in their southern distribution range: forest thinning could improve Scots pine’s ability to cope with stress, while pine removal may promote the growth of pubescent oak. Context Forested systems around the globe are being modified and climate change is one of the main drivers. Many regions of Spain, especially in the south and the east, where aridity is predicted to increase, could be some of the most vulnerable places for Scots pine (Pinus sylvestris L.) in Western Europe. In some cases, defoliation, mortality, and lack of regeneration of this species have induced a vegetation shift, as has been seen with Quercus spp. Adaptive forest management might help adjust the vulnerable forest systems to new climatic conditions. Aims This study, carried out in north-eastern Spain, applies silvicultural treatments to promote changes in species composition for improving the adaptation to climate change of a Scots pine mixed forest. The main objective is to evaluate how different silvicultural treatments give rise to more adapted stands in terms of survival, growth, and regeneration. Methods Three experimental treatments (and one control) were applied, two of them to reduce competition for Scots pine and a third pursuing the acceleration of replacement of Scots pine by pubescent oak (Quercus pubescens Willd.). The response of the stands to the treatments was monitored during 6 years. Results Mortality of Scots pine was nil or very low in the different treatments, but defoliation showed significant differences among treatments at the end of the study: 42% in the control treatment (CO), 25% in the understory clearing treatment (C), and 18% in the understory clearing and pine thinning treatment. The increment in the basal area of Scots pine between 2015 and 2021 did not show significant differences among silvicultural treatments (F = 3.9, p > 0.05), but that of pubescent oak was higher in the pine logging than in the other treatments. Regeneration of Scots pine and pubescent oak did not differ among silvicultural treatments. Conclusions These findings have relevant implications for the use of management to adapt forests to climate change: in its southern distribution range, forest thinning could improve the capacity of Scots pine to cope with stress conditions, whereas pine removal may promote pubescent oak.